Epitaxy and transport properties of alkali-earth palladate thin films - Yusuke Kozuka; Taisuke T. Sasaki; Terumasa Tadano; Jun Fujioka (Science and Technology of Advanced Materials)
Topological insulators and semimetals are an interesting class of materials for new electronic and optical applications owing to their characteristic electromagnetic responses originating from the spin-orbit coupled band structures. However, topological electronic structures are rare in oxide materials despite their chemical stability being preferable for applications. In this study, given the theoretical prediction of Dirac bands in CaPd3O4, we investigate the fabrication and transport properties of SrPd3O4 and CaPd3O4 thin films as candidates of oxide Dirac semimetals. We have found that these materials are epitaxially grown on MgO (100) substrate under limited growth conditions by pulsed laser deposition. The transport properties show a weak temperature dependence, suggestive of narrow-gap properties, although unintentionally doped holes hinder us from revealing the presence of the Dirac band. Our study establishes the basic thermodynamics of thin-film fabrication of these materials and will lead to interesting properties characteristic of topological band structure by modulating the electronic structure by, for example, chemical substitutions or pressure.